Deformation Controlled Fluid Mass‐Transfer Processes in Ancient Orogens - G. J. Hill; B. M. Frieman; E. A. Roots; P. E. Wannamaker; V. Maris; R. Haugaard; J. Kamm; R. Klanica; S. Kovacikova; A. J. Calvert; J. A. Craven; R. S. Smith (Geophysical Research Letters)
Abstract Despite abundant empirical evidence, the details of coupled deformation and mass transfer processes within a framework of the crustal architecture of ancient orogens remains enigmatic. Geophysical imaging of the Larder Lake‐Cadillac deformation zone, a well‐endowed crustal‐scale fault system in the Superior Province of the Canadian Shield, characterizes the crustal architecture and fault geometry of the system through the lower crust. By comparing the geophysically determined structure of the Larder Lake‐Cadillac deformation zone to stress changes induced by Archean (peak orogeny) rupture of the fault system, we show domains of earthquake‐triggered deformation coincide with the geophysically imaged low resistivity zones. These low resistivity zones likely formed due to Archean mineral bearing fluid migration from underlying fertile source zones to downstream (shallower) crustal reservoirs and, ultimately, near surface traps. The multi‐disciplinary approach identifies the syntectonic mass‐transfer processes and mineral bearing fluid pathways, providing an interpretive framework for unraveling the geophysical manifestation of the deformation controlled processes responsible for upflow of metalliferous fluids that may result in ore deposit formation in collisional orogens.